The Effect of Activating Prior Knowledge Strategies on Enhancing Law Students' Text Comprehension and Engagement in English Class (مجلة ديالى للبحوث الانسانية, 2021)
Language learning process builds on prior knowledge and what learners already know about certain topic, including terms and concepts, provides them with a foundation base for moving forwards and construct meaning. Making such connections to the text they are reading increases comprehension and helps them to be metacognitive. Such a process can be best achieved through applying a variety of classroom strategies for activating prior knowledge, or schema, which helps set a stage for new terms, concepts to be presented. Moreover, such strategies would help increase learners' engagement in classroom activities which involve their participation.